2016
DOI: 10.1007/s10964-016-0562-7
|View full text |Cite
|
Sign up to set email alerts
|

When Do Adolescents Accept or Defy to Maternal Prohibitions? The Role of Social Domain and Communication Style

Abstract: Drawing upon both Social-Cognitive Domain Theory and Self-Determination Theory, the goal of the present multi-informant study was to test whether the correlates of maternal prohibitions depend on what is prohibited (i.e., the content of the social domain involved), thereby contrasting moral with friendship prohibitions, as well on how the prohibition is communicated, thereby contrasting an autonomy-supportive with a controlling communication style. In a sample of adolescents (N = 196; mean age = 13.9 years; 63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 100 publications
(119 reference statements)
3
25
0
Order By: Relevance
“…As previous research suggests, parents' controlling communication style would relate to both more oppositional defiance (e.g., Chen et al, 2016;Van Petegem et al, 2016) and more submission (e.g., Assor & Tal, 2012; with regard to the parental request. By contrast, when parents communicate a request in an autonomy-supportive way, adolescents would be more likely to willfully adopt and accommodate to the parental request (Grolnick, 2003;Vansteenkiste et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…As previous research suggests, parents' controlling communication style would relate to both more oppositional defiance (e.g., Chen et al, 2016;Van Petegem et al, 2016) and more submission (e.g., Assor & Tal, 2012; with regard to the parental request. By contrast, when parents communicate a request in an autonomy-supportive way, adolescents would be more likely to willfully adopt and accommodate to the parental request (Grolnick, 2003;Vansteenkiste et al, 2014).…”
Section: Introductionmentioning
confidence: 80%
“…Personal issues, by contrast, are private aspects that pertain to adolescents' identity and are typically regulated by adolescents themselves, rather than by the parents (Nucci, 1996). Hence, whereas parental requests in the moral domain may be perceived less easily as a threat to the need for autonomy than requests in the academic domain, parental attempts at regulating the personal domain may especially be experienced as meddlesome and intrusive (see e.g., Kakihara & Tilton-Weaver, 2009;Smetana, 2006;Van Petegem et al, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…Findings from economic games suggest that feeling that one is seen to be a trusted partner fosters the desire to cooperate rather than defect in exchanges with others (Rabbie, 1991). More proximally, work expanding on psychological reactance theory (Brehm, 1966) has shown that the use of controls which restrict freedom elicit reactance (Vansteenkiste et al, 2014, see also Dillard & Shen, 2005Quick & Stephenson, 2008), perhaps due to a desire to restore independence in the absence of a feeling of choice (van Petegem et al, 2017). Such feelings might lead to behavior in opposition to wishes (Chartrand, Dalton, & Fitzsimons, 2007), and general behavior problems (Van Petegem et al, 2015).…”
Section: Reasons For Concealmentmentioning
confidence: 99%
“…In particular, parental regulation of personal issues (e.g., friendships) may be more challenging and may be experienced as more illegitimate and autonomy frustrating than parental regulation of academic issues (Smetana & Daddis, 2002;Soenens et al, 2009). In line with this assumption, recent research found that parental prohibitions about friendship issues (as opposed to moral issues) are more likely to be experienced as illegitimate and to trigger oppositional defiance (Van Petegem et al, 2017a). However, the correlates of an autonomy-supportive (as opposed to controlling) communication style were relatively similar across social domains.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…In line with this prediction, in a study making use of hypothetical scenarios of rule-breaking situations, Mageau et al (2018) found that autonomy-supportive strategies are perceived as more acceptable than psychologically controlling strategies. Similarly, in a study on parents' prohibitions in the domains of friendships and morality, Van Petegem et al (2017a) found that parental prohibitions are experienced as more legitimate when parents used an autonomy-supportive communication style. Taken together, theory and research indicate that parents' communication style may have implications for adolescents' appraisal of a situation of parental regulation of their academic behavior.…”
Section: Introductionmentioning
confidence: 94%